Evaluasi Koleksi Tercetak Bidang Manajemen Menggunakan Metode Conspectus - Suwardi Suwardi (Jurnal Pustaka Ilmiah)
A quality library collection supported by adequate services serves to expand the scope of knowledge, enhance independent thinking skills, integrate knowledge with reality, and promote the improvement of the cultural quality of its users. This means that the collection functions to enhance the quality of student graduates and support the realization of UII as rahmatan lil’alamin. The depth level of the collection is clearly mapped so that development goals and targets can be achieved. The conspectus method is an appropriate method used to evaluate collections related to the conditions surrounding the Library Division of FBE UII. This qualitative research uses a list-checking approach with the conspectus method. The population is the collection of printed books in the field of management, with instruments such as conspectus profiles, conspectus worksheets, and interview guidelines. The assessment was conducted by two evaluators from the management department faculty members. The collection is mapped in numerical levels using a ten-point scale or continuum from 0 if the library does not collect collections in a particular subject to 5 for collections at a comprehensive level. The evaluation results indicate a gap in the collection level of 8 levels between the lowest and highest levels. The gap in the average level of collection depth is based on the current collection category with an acquisition commitment of 0.57, an acquisition commitment with a collection goal of 1.86, and a current collection with a collection goal of 2.43.